A preliminary economic feasibility assessment of nuclear desalination in Madura Island. (4th May 2005) - Kim, S-H.; Hwang, Y-D.; Konishi, T.; Hastowo, Hudi
A joint study between KAERI and BATAN, which is entitled "A preliminary economic feasibility assessment of nuclear desalination in Madura Island", is being conducted under the framework of the Interregional Technical Cooperation Project of IAEA, signed on Oct. 10, 2001 at IAEA. The duration of the project is January 2002 to December 2004. An economic feasibility of nuclear desalination using system-integrated modular advanced reactor (SMART), which will provide Madura Island with electricity and potable water and also support industrialisation and tourism, will be assessed during the project. The scope of this joint study includes the analyses for the short- and long-term energy and water demand as well as the supply plan for Madura Island, evaluation of the site characteristics, environmental impacts and health aspects, technical and economic evaluation of SMART and its desalination system, including the feasibility of its being identified on the Madura Island. KAERI and BATAN are cooperating in conducting a joint study, and IAEA provides technical support and a review of the study products. This paper presents the interim results of the joint study by focussing on the technical and economic aspects of nuclear desalination using SMART in Madura Island.